KAJIAN NERACA AIR DAERAH IRIGASI CIHERANG KABUPATEN BANDUNG PROVINSI JAWA BARAT - An An Anisarida; Edward Hafudiansyah (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2022)
Ciherang Irrigation Area in Bandung is the location of the study. Based on data obtained, it showed water deficiency in the planting season 1 on October and in the planting season 2 on August. Thus, the study aimed to analyze the comparison between the availability of water and the need of water to get a proper cropping pattern implemented in the irrigation area. The availability of water was obtained from water debit that analyzed using the Weibull method while the need of water was determined by the availability of water for rice and palawija.. The results revealed that requirement of irrigation water in an existing cropping pattern of rice/palawija – rice/palawija – rice/palawija using the highest value of water demand at the weir intake gate (DR), 2,255 1/sec/ha, produced the total availability of water in an amount of 4,832 m3/sec while using the unit number for the implementation of operations in the field obtained the highest irrigation requirement value of 3,449 m3/sec. The alternative cropping pattern of rice – rice – palawija using the total value of water demand at the weir intake gate (DR), 2,436 1/sec/ha produced the availability of water in an amount of 5,261 m3/sec while using the unit number for the implementation of operations in the field obtained the highest irrigation requirement value in amount of 4,154 m3/sec.